When Guidelines Are Not Enough: Clinician Hesitation to Diagnose Borderline Personality Disorder in Adolescents as a Barrier to Timely Evidence‐Based Care - Samen Shahbaz (Personality and Mental Health, 2026)
ABSTRACT A recent review of 11 international clinical guidelines for borderline personality disorder (BPD) and its features in adolescents, found broad agreement on core recommendations: structured assessment, psychotherapy as first‐line treatment and family involvement. This is a meaningful step forward. But it raises a question the guidelines themselves do not answer: If clear recommendations exist, why are so many adolescents still not receiving a timely diagnosis? This commentary focuses on that gap. Clinicians frequently hesitate to diagnose BPD in young people, often out of concern about stigma or a belief that the diagnosis is premature or harmful. The evidence does not support these concerns. BPD features in adolescence are stable, clinically significant and respond to targeted treatment. When clinicians avoid the diagnosis, adolescents tend to receive fragmented, symptom‐focused care that misses the underlying presentation. There is a real paradox here: The attempt to protect young people from a label ends up denying them access to the treatment that label would unlock. This commentary argues that future guideline development must go beyond describing what good care looks like and start addressing why clinicians struggle to provide it.